Perfil da atividade de pesquisa publicada nos anais dos congressos brasileiros de pneumologia e tisiologia nos últimos vinte anos - Fabro, Alexandre Todorovic [UNESP]; Yoo, Hugo Hyung Bok [UNESP]; Queluz, Thais Helena Abrahão Thomaz [UNESP] (FapUNIFESP (SciELO), 2006)
Objective: To increase the knowledge base regarding pulmonology research in Brazil. Methods: A retrospective, observational study of the abstracts published in the Annals of the Brazilian Pulmonology and Phthisiology Conferences held from 1986 to 2004, quantifying the institutions of origin by geographic distribution and type, as well as categorizing the abstracts by study design and topic. Results: A total of 6467 abstracts were published. The institutions of origin were located, variously, in the Southeast (3870 abstracts), South (1309), Northeast (783), Central-West (267) and North (84). There were 94 abstracts originating from foreign institutions, especially from institutions in Portugal (56.3%) and the United States (13.8%). Most of the studies (5825) were conducted in public Brazilian institutions. There were 4234 clinical studies, 1994 case reports and 239 original research articles. A marked, progressive increase was observed in the number of clinical studies and case reports during the period evaluated. Overall, the most common themes were tuberculosis and other infections diseases (25.2%), following by oncology (11.6%), interstitial lung diseases (8.8%) and thoracic surgery (8.5%). Nevertheless, the number of abstracts on each topic varied widely from year to year. Conclusion: Public Brazilian institutions are the principal sources of pulmonology research in Brazil. Such research activity is concentrated in the southeastern part of the country. Case reports account for one-third of this activity. Although there was great variability in the subjects addressed, diseases that are highly prevalent in Brazil, such as tuberculosis and other infections diseases, were the most common topics.
Profile of research published in the annals of the Brazilian Pulmonology and Phthisiology Conferences held over the last twenty years
Keywords: Bibliometrics; Biomedical research/statistics & numerical data; Brazil; Pulmonary disease (Speciality); Respiratory tract diseases; Scientific and technical publications/statistics & numerical data; bibliometrics; documentation; human; medical research; organization; pulmonology; retrospective study; statistics; Abstracting and Indexing; Biomedical Research; Congresses; Humans; Pulmonary Disease (Specialty); Retrospective Studies